Konseling Kelompok Eksistensial Therapy dalam Perspektif Budaya dan Etika - Karnangsyah, Emi (Indonesian Journal of Counseling and Development, 2023)
This study explores the influence of culture and ethics in group counseling using Existential Therapy, utilizing a Systematic Literature Review (SLR) to evaluate 50 key articles. Findings reveal that participants' cultural backgrounds and the ethical norms held by both participants and therapists significantly affect the dynamics and outcomes of therapy. Culture shapes how participants interpret existential issues, while ethics ensure the integrity of the therapeutic process. The results suggest that a more culturally and ethically sensitive counseling approach can enhance the quality and effectiveness of group existential therapy. This research underscores the need for more contextual ethical guidelines and increased cultural awareness among counseling professionals to provide more inclusive and effective services.